Liver biopsy in the real world—reporting, expert concordance and correlation with a pragmatic clinical diagnosis. Issue 11 (25th October 2021) - Kim, Hannah P.; Idowu, Michael O.; Mospan, Andrea R.; Allmon, Andrew G.; Roden, Michael; Newsome, Philip; Lok, Anna S.; Thuluvath, Paul J.; Taunk, Jawahar; Fried, Michael W.; Sanyal, Arun J.; Barritt, A. Sidney; et al.
Summary: Background: Patients with non‐alcoholic steatohepatitis (NASH) and fibrosis stage ≥2 comprise a target population for pharmacotherapy. Liver biopsy, the reference standard for identifying this population, requires complete and accurate assessment of steatohepatitis and fibrosis. Aims To investigate the completeness of real‐world NASH‐related pathology reports, assess concordance between site pathologists and central expert interpretation of the histologic elements of NASH, and determine concordance between biopsy‐diagnosed NASH and a pragmatic clinical definition of NASH. Methods: Liver pathology reports from 222 patients across 38 TARGET‐NASH sites were analysed for documentation of the histologic features of NASH. Biopsy slides were over‐read by a blinded central expert pathologist. Concordance of histologic scores and interpretation was assessed. Histologic concordance with a clinical definition of NASH was determined. TARGET‐NASH clinically defined NASH: elevated ALT, hepatic steatosis on biopsy or imaging and ≥1 of the following: BMI ≥30 kg/m 2, type 2 diabetes mellitus and dyslipidaemia. Results: Documentation of steatosis, lobular inflammation, portal inflammation and ballooning were missing from 21%, 35%, 46% and 40% of reports, respectively. There was slight‐to‐fair concordance (weighted kappa 0.01‐0.35) between site and central pathologists for inflammatory features, and moderate concordance (weighted kappa 0.56‐0.57) for fibrosis staging. Clinical definition of NASH was 75%‐91% concordant (94%‐95% sensitive) with biopsy‐diagnosed NASH. Conclusions: There is substantial variability in reporting and grading NASH and fibrosis staging in clinical practice. This heterogeneity may adversely impact patient assessment and translation of practice guidelines into reality. The TARGET‐NASH pragmatic clinical definition may serve as a valuable tool to accurately identify NASH patients in clinical practice. Abstract : In a real world cohort of patients with NAFLD, liver biopsy reports were frequently missing key descriptive elements of steatosis, ballooning, and inflammation. Concordance between site and central pathologists ranged from slight to moderate for histological features of NASH and fibrosis. A pragmatic clinical definition of NASH was concordant and highly sensitive when compared with expert pathology assessment